In vivo production of engineered ACE2 decoy protects lungs from SARS-CoV-2 infection - Yuta Suzuki; Takayuki Miyazaki; Yoko Ida; Tatsuya Suzuki; Yumi Itoh; Shuto Nakao; Keita Kondo; Kenji Kubara; Keisuke Nishioka; Hiroki Muto; Ryuji Watari; Toshifumi Hirayama; et al. (Molecular Therapy: Nucleic Acids)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) variants repeatedly evade the immune system within short periods. Thus, next-generation therapeutics that are resistant to mutations and can be rapidly supplied to individuals in an emergency are required. Here, we designed an mRNA encoding an engineered angiotensin-converting enzyme 2 (ACE2) decoy, 3N39v4, composed of high-affinity ACE2 and a human immunoglobulin G Fc domain. The 3N39v4-encoded mRNA was encapsulated in lipid nanoparticles for efficient in vivo delivery. Systemic delivery of mRNA in mice resulted in a dose-dependent expression of 3N39v4 in plasma (20–261 μg/mL at 1–10 mg/kg) with sufficient tolerability. An improved pharmacokinetic profile of the produced protein was compared to injection of the 3N39v4 protein. In vivo-expressed 3N39v4 exhibited broad neutralization against nine SARS-CoV-2 variants and other sarbecoviruses, including the currently circulating Omicron subvariants JN.1 and BA.2.86. A single intravenous injection of 3N39v4-encoded mRNA resulted in a robust, dose-dependent improvement in the outcomes of mice infected with SARS-CoV-2. The mRNA treatment in monkeys produced 3N39v4 in sera, which inhibited the replication of the authentic viruses. The rapid development of mRNA drugs highlights the potential of mRNA-encoded ACE2 decoys in emergencies to combat diverse SARS-CoV-2 variants, including future variants.